2015
DOI: 10.1021/acs.energyfuels.5b00021
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Change of Green Coke to Calcined Coke Using Qingdao High-Sulfur Petroleum Coke

Abstract: This paper presents macromolecular models of sulfur-containing Qingdao petroleum. The results were investigated with ultimate analysis, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy. The models showed that organic sulfur, nitrogen, and oxygen in the coke were mainly in the forms of thiophene-containing polycyclic aromatic hydrocarbon, polycyclic aromatic hydrocarbons containing pyrrole or pyridine, and CO or C–O–C, respectively. During calcination, the aromaticity of coke incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
0
37
1
Order By: Relevance
“…Despite sulfur's positive effect on the carboxy reactivity, too high levels of S are unwanted because they leave the cell as environmentally unfriendly gases. In CPC in some cases sulfur has been observed as a thiophene-containing polycyclic aromatic hydrocarbons [12][13][14][15]. In the high sulfur cokes studied here for metal impurities, a previous study has shown that the sulfur is present as elemental sulfur or at least contains S-S bonds [16].…”
Section: Introductionmentioning
confidence: 80%
“…Despite sulfur's positive effect on the carboxy reactivity, too high levels of S are unwanted because they leave the cell as environmentally unfriendly gases. In CPC in some cases sulfur has been observed as a thiophene-containing polycyclic aromatic hydrocarbons [12][13][14][15]. In the high sulfur cokes studied here for metal impurities, a previous study has shown that the sulfur is present as elemental sulfur or at least contains S-S bonds [16].…”
Section: Introductionmentioning
confidence: 80%
“…[16] The proportions of S-S bound sulfur (identified from S 8 in the LCF) vary between the different cokes from 16 to 53 pct of the total S giving 0.3 to 2.3 wt pct of this kind of sulfur in the cokes. The exact kind of compound is unknown, but large amounts of sulfides with sulfur in the oxidation state À 1 (e.g., FeS 2 ) are unlikely due to the much higher quantity of sulfur vs metals (Figure 7(d)).…”
Section: Discussionmentioning
confidence: 99%
“…[16] These may also contain some thiazines. Limited information can be obtained on the organic sulfur standards using the K-edge.…”
Section: E(evmentioning
confidence: 99%
See 1 more Smart Citation
“…The brominated process and the complete reaction mechanisms of mercury removal by simulation were presented. As shown in Figure 8 , these edge models were selected from the large molecular structure of uncalcined petroleum coke [ 69 ]. Generally, the standard to distinguish whether it is physical or chemical adsorption is the adsorption energy of 42 KJ/mol.…”
Section: Micro-scale Mechanism Of Physical-chemical Evolution Of Hspc...mentioning
confidence: 99%